FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DALAM INDEKS IDX QUALITY30 - Jhon Lismart Benget. P.; Tina Novianti Sitanggang; Hotma Mentalita (Politeknik Bisnis Indonesia, 2022)
Abstract The purpose of this study is to examine the effect of inflation, company size, debt to equity ratio and total asset turnover on the financial performance. The population of this study is the IDX Quality30 Index which were listed on the Indonesia Stock Exchange in 2018-2021. The results of this study indicate that simultaneously inflation, company size, debt to equity ratio and total asset turnover affect the financial performance. Partially, this study show total asset turnover has a positive and significant effect on the financial performance. Company size and debt to equity ratio has a negative and significant effect on the financial performance while inflation has no significant effect on the financial performance. Keywords: Inflation, Company Size, Debt to Equity Ratio, Total Asset Turnover, Financial Performance